Effect of plate color on dietary intake in young people with mild intellectual disabilities : Plate color and intellectual disability - Jung, Eun Young; Kim, Woon Ji; Park, Eun Young (Progress in Nutrition, 2021)
This study aimed to investigate whether plate color affects dietary intake in young people with mild intellectual disabilities. The experiment employed a within-subjects, repeated-measures design. A portion of fried rice (400 g) was presented on a white plate, red plate, or blue plate. Twenty subjects (12 male, 8 female; aged 15–21 years) took part. Although the amount served was always the same, most of the subjects (80%) estimated that the amount of fried rice on a white plate was more than the amount in a regular rice bowl. In contrast, 50% or 40% of the subjects perceived the amount of fried rice on the red or blue plate, respectively, to be more than the amount in a regular rice bowl. Plate color did not have a significant effect on the amount consumed. There were no significant differences in satiety and hunger ratings across conditions for 2 hours after each test meal. Young people with intellectual disabilities, who are less influenced by the environment as a result of their cognitive deficits, may be forced to rely more on internal factors than on external factors.